Justice as a Factor of Social Integrity - Muravyev, Victor V. (European Journal of Multidisciplinary Studies, 2019)
The idea of social justice is universal for religious and secular ideologies. Sources of it may be divided in two kinds: natural and cultural. Natural sources are: laws of The Universe and human nature. Cultural sources are: holy texts and revelations, actions and teachings of holy messengers and wise men. Named sources may be combined at particular religious, moral, politic teachings and models of society organization
Keywords: wealth and poverty; justice; fair society; social equality